Synthesis and Tribological characteristics of a nano CuO particle-filled water-based lubricants. Issue 1 (October 2020) - Rajmohan, T.; Hemanth Kumar, D.; Nivithetha, R.; Elamburthi,; Kalyan Chakravarthy, V.V.
Abstract: The oil-based lubricating system tends to produce high cutting temperatures owning to the low cooling capability of oil lubricants. The addition of lubricating additives in nanoscale could increase the tribological and lubrication performance of the water-based lubricants. In this work, nano CuO particle-filled water-based lubricants as cutting fluids were developed using ultrasonication process. The Thermophysical Properties of synthesized nano filled water-based lubricant was tested and analyzed. The tribological characteristics were fairly investigated using four-ball and pin on disc apparatus testing units. The results indicated that nano CuO filled water-based lubricant shows enhanced tribological performance in terms of coefficient of friction (COF) and wear scar diameter (WSD) compared with base coolant. The superior performance of CuO filled water-based lubricant was credited to the detail that CuO nanoparticle additives arrived the rubbing interface and made a tribo-thin layer of CuO. Water-based lubricant showed the highest surface deformation compared to nano-based lubricants which indicate that the damage was due to adhesive wear.